Influence of Social Class and Identity on The Characters in the Novel the Great Gatsby. - Nowamukama, Blessing (Kabale University, 2024)
The study assessed the influence of social class and identity on the characters in the novel. The Great Gatsby follows the objectives of the study which were to analyze how characters in the novel are affected by their social standing, to explore the differences between characters from various social classes, and to discuss the narrative techniques that depict social class in the novel. The study adopted a case study research design. The findings of the study show that Gatsby's social standing profoundly affects his life and ambitions. The study concluded that characters in The Great Gatsby are profoundly influenced by their social standing, which affects their behaviors, motivations, and interactions. Gatsby’s relentless pursuit of wealth and social status exemplifies how social class aspirations drive personal ambitions and ultimately lead to personal downfall. The study recommended that teachers should provide learners with sufficient awareness of the stylistics theories as well as the applied linguistic theories